2003
DOI: 10.1046/j.1440-1819.2003.01153.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deterioration and changes of P300 during total sleep deprivation

Abstract: The study was conducted to evaluate the cognitive deteriorations induced by sleep deprivation with the computerized neurocognitive tests and the P300 event-related potential. Thirty healthy college students (22 men, eight women) participated in the present study. Subjects remained awake for 38 h under continuous surveillance. In the morning and the evening of the two study days, the computerized neurocognitive tests and the P300 were performed. In vigilance test and reaction unit test, there were significant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 18 publications
6
41
1
3
Order By: Relevance
“…There is increasing evidence from experimental and epidemiologic studies in the general population that sleep quality is associated with cognitive function (5)(6)(7)(8)(9). Although pervasive sleep difficulty has been documented widely among dialysis patients (10 -14), we identified only one study that considered the potential association of sleep difficulty with cognitive function.…”
mentioning
confidence: 99%
“…There is increasing evidence from experimental and epidemiologic studies in the general population that sleep quality is associated with cognitive function (5)(6)(7)(8)(9). Although pervasive sleep difficulty has been documented widely among dialysis patients (10 -14), we identified only one study that considered the potential association of sleep difficulty with cognitive function.…”
mentioning
confidence: 99%
“…In these patients, one or both of hypoxia and sleep deprivation seem to alter memory process, leading to increase in delay and decrease amplitude of P300 wave in the ERP recordings. Accordingly, it causes reduced vigilance and increased time to react (35)(36)(37). It was observed that latency decreased and amplitude increased.…”
Section: Discussionmentioning
confidence: 99%
“…Latency is associated to the interstimuli frequency to the individual's attention and concentration 15,25 . The studies which showed a significant delay in P300 latency had individuals with severe OSAS 13 , of sleep deprivation associated with forced awakeness 6 and because of their circadian cycle phase 17 . On the other hand, a study involving individuals with OSAS showed that the attention deficit is more severe in young people, when compared to elderly (threshold age: 50 years), and that age it does not interact with OSAS in worsening the cognitive deficit 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Case-control clinical studies carried out with individuals subjected to a forced sleep deprivation showed latency extension and reduction in the auditory P300 amplitude in the study group. These results have suggested that the P300 changes in the study group were reflexes from lowering the state of awareness, which extends the reaction time [4][5][6] . The cognitive deterioration induced by sleep deprivation is a consequence of neurophysiological changes, demonstrated by reduction in amplitude and increase in P300 latency.…”
Section: Introductionmentioning
confidence: 99%